Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Alright, let's dive into the question step by step.
Given the functions:
[tex]\[ f(x) = 2x - 3 \][/tex]
[tex]\[ g(x) = 3x^2 - 4 \][/tex]
We need to find:
a. The composition [tex]\((f \circ g)(x)\)[/tex]
b. The composition [tex]\((g \circ f)(x)\)[/tex]
c. The value of [tex]\((f \circ g)(2)\)[/tex]
### a. Finding [tex]\((f \circ g)(x)\)[/tex]
The composition [tex]\((f \circ g)(x)\)[/tex] means we want to apply [tex]\(g(x)\)[/tex] first and then apply [tex]\(f\)[/tex] to the result of [tex]\(g(x)\)[/tex].
Start by calculating [tex]\(g(x)\)[/tex]:
[tex]\[ g(x) = 3x^2 - 4 \][/tex]
Now, apply [tex]\(f\)[/tex] to [tex]\(g(x)\)[/tex]:
[tex]\[ (f \circ g)(x) = f(g(x)) = f(3x^2 - 4) \][/tex]
Substitute [tex]\(3x^2 - 4\)[/tex] into [tex]\(f(x)\)[/tex]:
[tex]\[ f(3x^2 - 4) = 2(3x^2 - 4) - 3 \][/tex]
[tex]\[ = 6x^2 - 8 - 3 \][/tex]
[tex]\[ = 6x^2 - 11 \][/tex]
So, [tex]\((f \circ g)(x) = 6x^2 - 11\)[/tex].
### b. Finding [tex]\((g \circ f)(x)\)[/tex]
The composition [tex]\((g \circ f)(x)\)[/tex] means we want to apply [tex]\(f(x)\)[/tex] first and then apply [tex]\(g\)[/tex] to the result of [tex]\(f(x)\)[/tex].
Start by calculating [tex]\(f(x)\)[/tex]:
[tex]\[ f(x) = 2x - 3 \][/tex]
Now, apply [tex]\(g\)[/tex] to [tex]\(f(x)\)[/tex]:
[tex]\[ (g \circ f)(x) = g(f(x)) = g(2x - 3) \][/tex]
Substitute [tex]\(2x - 3\)[/tex] into [tex]\(g(x)\)[/tex]:
[tex]\[ g(2x - 3) = 3(2x - 3)^2 - 4 \][/tex]
First, expand [tex]\((2x - 3)^2\)[/tex]:
[tex]\[ (2x - 3)^2 = 4x^2 - 12x + 9 \][/tex]
Then, substitute back into [tex]\(g(x)\)[/tex]:
[tex]\[ g(2x - 3) = 3(4x^2 - 12x + 9) - 4 \][/tex]
[tex]\[ = 12x^2 - 36x + 27 - 4 \][/tex]
[tex]\[ = 12x^2 - 36x + 23 \][/tex]
So, [tex]\((g \circ f)(x) = 12x^2 - 36x + 23\)[/tex].
### c. Finding [tex]\((f \circ g)(2)\)[/tex]
Now, we need to find the value of [tex]\((f \circ g)(2)\)[/tex]:
Start by calculating [tex]\(g(2)\)[/tex]:
[tex]\[ g(2) = 3(2)^2 - 4 \][/tex]
[tex]\[ = 3(4) - 4 \][/tex]
[tex]\[ = 12 - 4 \][/tex]
[tex]\[ = 8 \][/tex]
Next, use this result in [tex]\(f\)[/tex]:
[tex]\[ f(g(2)) = f(8) \][/tex]
[tex]\[ f(8) = 2(8) - 3 \][/tex]
[tex]\[ = 16 - 3 \][/tex]
[tex]\[ = 13 \][/tex]
So, [tex]\((f \circ g)(2) = 13\)[/tex].
### Summary:
a. [tex]\((f \circ g)(x) = 6x^2 - 11\)[/tex]
b. [tex]\((g \circ f)(x) = 12x^2 - 36x + 23\)[/tex]
c. [tex]\((f \circ g)(2) = 13\)[/tex]
Given the functions:
[tex]\[ f(x) = 2x - 3 \][/tex]
[tex]\[ g(x) = 3x^2 - 4 \][/tex]
We need to find:
a. The composition [tex]\((f \circ g)(x)\)[/tex]
b. The composition [tex]\((g \circ f)(x)\)[/tex]
c. The value of [tex]\((f \circ g)(2)\)[/tex]
### a. Finding [tex]\((f \circ g)(x)\)[/tex]
The composition [tex]\((f \circ g)(x)\)[/tex] means we want to apply [tex]\(g(x)\)[/tex] first and then apply [tex]\(f\)[/tex] to the result of [tex]\(g(x)\)[/tex].
Start by calculating [tex]\(g(x)\)[/tex]:
[tex]\[ g(x) = 3x^2 - 4 \][/tex]
Now, apply [tex]\(f\)[/tex] to [tex]\(g(x)\)[/tex]:
[tex]\[ (f \circ g)(x) = f(g(x)) = f(3x^2 - 4) \][/tex]
Substitute [tex]\(3x^2 - 4\)[/tex] into [tex]\(f(x)\)[/tex]:
[tex]\[ f(3x^2 - 4) = 2(3x^2 - 4) - 3 \][/tex]
[tex]\[ = 6x^2 - 8 - 3 \][/tex]
[tex]\[ = 6x^2 - 11 \][/tex]
So, [tex]\((f \circ g)(x) = 6x^2 - 11\)[/tex].
### b. Finding [tex]\((g \circ f)(x)\)[/tex]
The composition [tex]\((g \circ f)(x)\)[/tex] means we want to apply [tex]\(f(x)\)[/tex] first and then apply [tex]\(g\)[/tex] to the result of [tex]\(f(x)\)[/tex].
Start by calculating [tex]\(f(x)\)[/tex]:
[tex]\[ f(x) = 2x - 3 \][/tex]
Now, apply [tex]\(g\)[/tex] to [tex]\(f(x)\)[/tex]:
[tex]\[ (g \circ f)(x) = g(f(x)) = g(2x - 3) \][/tex]
Substitute [tex]\(2x - 3\)[/tex] into [tex]\(g(x)\)[/tex]:
[tex]\[ g(2x - 3) = 3(2x - 3)^2 - 4 \][/tex]
First, expand [tex]\((2x - 3)^2\)[/tex]:
[tex]\[ (2x - 3)^2 = 4x^2 - 12x + 9 \][/tex]
Then, substitute back into [tex]\(g(x)\)[/tex]:
[tex]\[ g(2x - 3) = 3(4x^2 - 12x + 9) - 4 \][/tex]
[tex]\[ = 12x^2 - 36x + 27 - 4 \][/tex]
[tex]\[ = 12x^2 - 36x + 23 \][/tex]
So, [tex]\((g \circ f)(x) = 12x^2 - 36x + 23\)[/tex].
### c. Finding [tex]\((f \circ g)(2)\)[/tex]
Now, we need to find the value of [tex]\((f \circ g)(2)\)[/tex]:
Start by calculating [tex]\(g(2)\)[/tex]:
[tex]\[ g(2) = 3(2)^2 - 4 \][/tex]
[tex]\[ = 3(4) - 4 \][/tex]
[tex]\[ = 12 - 4 \][/tex]
[tex]\[ = 8 \][/tex]
Next, use this result in [tex]\(f\)[/tex]:
[tex]\[ f(g(2)) = f(8) \][/tex]
[tex]\[ f(8) = 2(8) - 3 \][/tex]
[tex]\[ = 16 - 3 \][/tex]
[tex]\[ = 13 \][/tex]
So, [tex]\((f \circ g)(2) = 13\)[/tex].
### Summary:
a. [tex]\((f \circ g)(x) = 6x^2 - 11\)[/tex]
b. [tex]\((g \circ f)(x) = 12x^2 - 36x + 23\)[/tex]
c. [tex]\((f \circ g)(2) = 13\)[/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.